Learning for life and/or work : the status quo of pre-vocational education in India, China, Germany and the USA - Pilz, Matthias [Verfasser]; Krisanthan, Balasundaram [Verfasser]; Michalik, Björn [Verfasser]; Zenner, Lea [Verfasser]; Li, Junmin [Verfasser] (My University, 2016)
"The role of pre-vocational education in general compulsory education has become increasingly relevant over recent years, with the international debate focussing particularly on its importance in school-to-work transitions. This study considers curriculum design and the implementation of pre-vocational education in four countries with radically different cultures: India, China, Germany and the USA. Using a theoretically framed concept of relevance to inform curriculum analysis, it compares the widely divergent content of curricula. In addition to this, interviews with teachers in all four countries flesh out how the curriculum is implemented in practice. The study, which is based on the 'prescribed curriculum' and 'enacted curriculum' approach, demonstrates that a range of factors means implementation varies widely from country to country but that teachers in all four countries focus in pre-vocational education on equipping students with life-skills." (Authors' abstract, BIBB-Doku)

Der Stellenwert von vorberuflicher Bildung in den letzten beiden Jahren der Pflichtschulzeit hat über die internationale Debatte zu Übergangen von der Schule in die Arbeitswelt an Bedeutung gewonnen. Für den im deutschen Kontext vielfach mit den Begriffen "Arbeitslehre" oder "Technikunterricht" bzw. "Wirtschaftskunde" bezeichneten Untersuchungsgegenstand hat sich im internationalen Kontext der Begriff "pre-vocational education" etabliert. Diese Studie untersucht das Design und die Implementierung von Curricula vorberuflicher Bildung in vier Ländern mit grundlegend unterschiedlichen Kulturen: Indien, China, Deutschland und die USA. Die Studie basiert auf dem "prescribed curriculum"- und "enacted curriculum"-Ansatz. Mittels einer theoretisch fundierten Curriculumanalyse werden Ziele und Inhalt der Curricula der vier Länder in einem ersten Schritt verglichen. Halbstandardisierte Interviews mit Lehrkräften aus den vier Ländern liefern in einem zweiten Schritt Erkenntnisse über die Umsetzung im Schulalltag. (BIBB-Doku)
Keywords: S 1.2.2 Schulische Maßnahmen der Berufsvorbereitung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.3.4 Asien; I 2.3.2 Nordamerika; Allgemeinbildende Schule; Berufsvorbereitung; Ökonomische Bildung; Curriculum; Analyse; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Bundesrepublik Deutschland; China; Indien; USA